How to marry a cowboy - McDavid, Cathy, 1956- (McDavid, Cathy, 1956- Wishing Well Springs., 2021)
Coming home means...confronting her former crush. Trick rider Kenna Hewitt can't avoid the company of Channing Pearce--not when the handsome cowboy needs Kenna's help saving his family's rodeo arena. Working together, and being in a wedding together, soon has old feelings resurfacing. But as a gal who does stunts for a living, trusting in a possible future with the cowboy of her dreams is still the most dangerous task she's ever faced...